Wireless video capsule enteroscopy in preclinical studies: methodical design of its applicability in experimental pigs - Kopácová, Marcela; Tachecí, Ilja; Kvetina, Jaroslav; Bures, Jan; Kunes, Martin; Spelda, Stanislav; Tycová, Vera; Svoboda, Zbynek; Rejchrt, Stanislav (Digestive diseases and sciences, 2010)
The aim of this project was to develop a methodology to introduce wireless video capsule endoscopy in preclinical research. Five mature female pigs (Sus scrofa domestica) were selected for the study. Capsule endoscopes (the EndoCapsule system; Olympus) were introduced into the duodenum endoscopically in each of the animals. The life span of batteries (i.e., total time of endoscopy recording) was 487-540 min (median 492 min). The capsule endoscope reached the cecum during enteroscopy once (after 7 h 57 min), in the remaining cases, endoscopy recordings terminated in the distal or terminal ileum. All capsule enteroscopies found a normal pattern of the small intestine. The intestinal lumen is narrower, transverse folds are sparse or even absent, villi are wider but less prominent in pigs compared to humans. Capsule endoscopy in experimental pigs will be helpful for future trials on injury of different drugs and xenobiotics to the small bowel.
Keywords: Capsule Endoscopy; Swine; prasata; ženské pohlaví; tenké střevo; zvířata; Endoscopy, Gastrointestinal; Female; Intestine, Small; gastrointestinální endoskopie; kapslová endoskopie; Animals